The Relationship of Waiting Time to Outpatient Satisfaction in the Work Area Puskesmas Popayato - Euis Herawati Hidayat; Arifandi Pelealu; Septia Ningsi Polumulo (PROMOTOR, 2023)
One form of quality of service that patients often complain about is waiting times. Waiting time is the length of time patients wait for health services until they are examined by a doctor.  The patient's time will affect the patient's assessment of service satisfaction at the Puskesmas.waiting time is divided into three, namely the patient's waiting time when registering at the counter to get a queue number, the patient's waiting time to get a doctor's examination, the patient's waiting time to get medicinepatient satisfaction is a person's feeling of pleasure derived from the comparison between pleasure in the activity of a product with his expectations. See from 5 aspects of quick response, reliability, assurance, empathy, physical evidence. The purpose of the study was to determine the relationship  of waiting time to outpatient satisfaction. Quantitative research  design with cross sectional approach. The population is 80 patients who visit the Popayato Health Center. The sample size is 80 outpatients or total sampling. The results showed that the waiting time in terms of waiting time for patient registration was the most fast waiting time which was 65 people (81.25%) and dissatisfied as many as 1 person (1.25%) while patients who said long waiting time with satisfaction category satisfied as many as 2 people (2.25%) and dissatisfied as many as 12 people (15%) with a value of pValue = 0.000<0.05. Suggestions are expected to Puskemas Popayato to be able to evaluate patient satisfaction and take actions to increase patient satisfaction and take actions to increase patient satisfaction specifically and improve service quality in general.